Design of a measurement device for air pollution concentrations using an open-source electronics software and hardware system - Wahid, Herman (International Journal of Integrated Engineering, 2017)
Contaminates air killed million people each year and incurs a cost of living on medical treatment. Normally, the authority manages the environmental control by practicing the air quality monitoring strategy by using high-end instrumentations which were very costly and requires periodical maintenance. In this paper, a lowcost air quality monitoring system has been proposed to monitor the air quality. The system is an Arduino based device which is consisting of carbon monoxide sensor, ozone sensor, dust sensor, sulphur dioxide sensor, nitrogen dioxide sensor, temperature and humidity sensor and anemometer. The system is capable to monitor air quality such as carbon monoxide, sulphur dioxide, nitrogen dioxide and meteorological condition such as temperature and humidity. The average level of gas pollution, such as NO2 and ozone was recorded at 10.31 ppm and 17.31 ppm respectively. The developed device will help to monitor air quality in the residence and workplace environment. This system fills the gap between cost efficiency and reliability of other system architectures.